Association of Base Excision Repair Gene Polymorphisms with ESRD Risk in a Chinese Population. (6th June 2012) - Cai, Zhenming; Chen, Huimei; Tao, Jing; Guo, Wenwen; Liu, Xiufang; Zheng, Bixia; Sun, Wei; Wang, Yaping
Abstract : The base excision repair (BER) pathway, containing OGG1, MTH1 and MUTYH, is a major protector from oxidative DNA damage in humans, while 8-oxoguanine (8-OHdG), an index of DNA oxidation, is increased in maintenance hemodialysis (HD) patients. Four polymorphisms of BER genes, OGG1 c.977C > G (rs1052133), MTH1 c.247G > A (rs4866), MUTYH c.972G > C (rs3219489), and AluYb8MUTYH (rs10527342), were examined in 337 HD patients and 404 healthy controls. And the 8-OHdG levels in leukocyte DNA were examined in 116 HD patients. The distribution of MUTYH c.972 GG or AluYb8MUTYH differed between the two groups and was associated with a moderately increased risk for end-stage renal disease (ESRD) (P = 0.013 and 0.034, resp.). The average 8-OHdG/10 6 dG value was significantly higher in patients with the OGG1 c.977G, MUTYH c.972G or AluYb8MUTYH alleles (P < 0.001 via ANOVA). Further analysis showed that combination of MUTYH c.972GG with OGG1 c.977GG or AluYb8MUTYH increased both the risk for ESRD and leukocyte DNA 8-OHdG levels in HD patients. Our study showed that MUTYH c.972GG, AluYb8MUTYH, and combination of OGG1 c.977GG increased the risk for ESRD development in China and suggested that DNA oxidative damage might be involved in such process.